2020
DOI: 10.2147/vhrm.s240500
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Significance of Factor XIII Activity and Monocyte-Derived Microparticles in Cancer Patients</p>

Abstract: Background: The aim was to evaluate factor XIII activity (FXIIIa) and monocyte-derived microparticles (MDMPs) in cancer patients. Methods: In total, 138 cancer patients (31 malignant lymphomas, 39 multiple myelomas, and 68 lung cancers) were analyzed. We measured various biomarkers including FXIIIa and MDMPs. Results: The values of endothelial activation markers, monocyte chemoattractant peptide (MCP)-1, soluble (s)CD14, and MDMPs were higher in cancer patients than in noncancerous controls. MCP-1, sCD14, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…TGM1 was also upregulated in tumor cell aggregates (spheroids) exhibiting low chemosensitivity in ovarian cancer peritoneal uid (43). F13A1 has been identi ed as biomarkers of dismal prognosis in various types of cancers (35,44,45) and promotes the metastasis of melanoma as well as lung squamous cell carcinoma(46, 47). As a well-characterized transamidase, TGM2 can not only promote protein cross-linking by catalyzing post-translational modi cations of proteins, but also function as a G-protein coupled membrane receptor (GTPase), deamidase, adapter/scaffold, protein disul de isomerase, isopeptidase, and kinase (24,(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…TGM1 was also upregulated in tumor cell aggregates (spheroids) exhibiting low chemosensitivity in ovarian cancer peritoneal uid (43). F13A1 has been identi ed as biomarkers of dismal prognosis in various types of cancers (35,44,45) and promotes the metastasis of melanoma as well as lung squamous cell carcinoma(46, 47). As a well-characterized transamidase, TGM2 can not only promote protein cross-linking by catalyzing post-translational modi cations of proteins, but also function as a G-protein coupled membrane receptor (GTPase), deamidase, adapter/scaffold, protein disul de isomerase, isopeptidase, and kinase (24,(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, a decrease in plasma factor XIIIa suggests a quantitative biomarker dynamics deviation towards hypocoagulability, i.e a reduced potential for the stabilization of fibrins in the final step of the coagulation pathway; however, factor XIIIa deficiency classification is not met until percent activity declines to less than 1%. 33,34 Thus, despite significant differences among the two groups, the relatively preserved percent activity of factor XIIIa within the lymphoma group suggests adequate clot stabilization potential, however, there is an inherent lack in previous studies which have explored this phenomenon in lymphoma patients. Limited data generated by Adany et al suggested tumorassociated macrophages containing factor XIII to exist as a nonhomogeneous population with varying protein expressivity.…”
Section: Thrombo-inflammatory Biomarkersmentioning
confidence: 99%
“…Coagulation abnormalities are common in patients with metastatic oncological disease [13]. The relationship between FXIII and NSCLC is controversial, with some authors describing an increased activity of FXIII in patients with this neoplasm [7,8]. Given the initial picture of priapism in a patient with NSCLC, there was a suspicion of disseminated intravascular coagulation (DIC).…”
Section: Globalize Your Researchmentioning
confidence: 99%
“…The relationship between FXIII and non-small cell lung cancer (NSCLC) is controversial, with some authors describing an increased activity of FXIII in such cases [7,8]. This is a case report of a male patient with metastatic NSCLC and FXIII deficiency, which is a challenging diagnosis that requires a high index of clinical suspicion in the presence of normal routine coagulation tests (APTT, PT and fibrinogen).…”
Section: Introductionmentioning
confidence: 99%